2014
DOI: 10.1016/j.biopsych.2014.03.026
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Intranasal Ketamine in Major Depressive Disorder

Abstract: Background The N-methyl-d-aspartate glutamate receptor antagonist ketamine, delivered via an intravenous route, has shown rapid antidepressant effects in patients with treatment-resistant depression. The current study was designed to test the safety, tolerability and efficacy of intranasal ketamine in patients with depression who had failed at least one prior antidepressant trial. Methods Twenty patients with major depression were randomized and 18 completed two treatment days with intranasal ketamine hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
360
4
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(381 citation statements)
references
References 35 publications
8
360
4
9
Order By: Relevance
“…However, alternative routes of administration need to be considered for clinical practice. The first controlled randomized, double-blind, crossover study in 20 patients with major depression reported significant improvements in symptoms (based on the Montgomery-Å sberg Depression Rating Scale) 24 h after intranasal administration of ketamine hydrochloride (50 mg) [61]. The advantage of intranasal administration over intravenous administration is that the intranasal route produces rapid antidepressant effects (within 5-40 min) with fewer dissociative side-effects and no drug-induced euphoria [62].…”
Section: Other Clinical Concernsmentioning
confidence: 99%
“…However, alternative routes of administration need to be considered for clinical practice. The first controlled randomized, double-blind, crossover study in 20 patients with major depression reported significant improvements in symptoms (based on the Montgomery-Å sberg Depression Rating Scale) 24 h after intranasal administration of ketamine hydrochloride (50 mg) [61]. The advantage of intranasal administration over intravenous administration is that the intranasal route produces rapid antidepressant effects (within 5-40 min) with fewer dissociative side-effects and no drug-induced euphoria [62].…”
Section: Other Clinical Concernsmentioning
confidence: 99%
“…INDD can improve the convenience of drug administration, as with intranasally administered ketamine 17 in place of intravenously infused ketamine for patients with refractory depression. Table 2 lists a few examples of INDD applications in neuropsychiatry; in this regard, ketamine and oxytocin are perhaps the best-studied agents.…”
Section: Improvement Of Bioavailabilitymentioning
confidence: 99%
“…A case report also showed benefits with intranasal ketamine in depression. 35 In a randomized, double-blind, saline-controlled, crossover trial conducted in 20 patients with major depression, Lapidus et al 17 found that a single intranasal dose of ketamine (50 mg) outperformed saline by 7.6 points on the Montgomery-Asberg Depression Rating Scale as assessed 24 hours after dosing; the response rate was 44% vs 6%, respectively. Anxiety ratings also decreased significantly more with ketamine.…”
Section: Intranasal Ketaminementioning
confidence: 99%
“…While more work is needed to further explore repeated dosing, other studies have examined alternative methods of delivery: oral [Irwin and Iglewicz, 2010;Paslakis et al 2010;Irwin et al 2013;De Gioannis and De Leo, 2014], intramuscular [Cusin et al 2012], sublingual [Lara et al 2013], and most recently, intranasal [Lapidus et al 2014], which will be reviewed in detail as follows.…”
Section: Alternative Modes Of Administrationmentioning
confidence: 99%